RESPONSIBILITY POLICY PEMERINTAH KABUPATEN INDRAGIRI HILIR TERHADAP ANAK JALANAN - Vivi Arfiani Siregar,; Jamri,; Indra Mukhlis Adnan,; Muannif Ridwan, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The government's role in eradicating beggars in Indragiri Hilir Regency is primarily focused on the policies implemented by the government. The strategy is founded on a comprehensive analysis. Human life is replete with communication activities. Communication becomes critical in conveying one's thoughts, feelings, ideas, and life problems.